2020
DOI: 10.1016/s1473-3099(20)30371-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for SARS-CoV-2 among patients in the Oxford Royal College of General Practitioners Research and Surveillance Centre primary care network: a cross-sectional study

Abstract: Background There are few primary care studies of the COVID-19 pandemic. We aimed to identify demographic and clinical risk factors for testing positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) within the Oxford Royal College of General Practitioners (RCGP) Research and Surveillance Centre primary care network. MethodsWe analysed routinely collected, pseudonymised data for patients in the RCGP Research and Surveillance Centre primary care sentinel network who were tested for SARS-CoV-2 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
567
18
30

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 583 publications
(676 citation statements)
references
References 43 publications
61
567
18
30
Order By: Relevance
“…In accordance, our analysis identified several diagnostic categories that are significantly positively associated with a positive SARS-CoV-2 PCR test result, including diabetes, heart disease, obesity, and anemia, all of which others have also found to be associated with increased risk of COVID-19 hospitalizations ( Figure 2 A and Supplementary Table 1). 25 Relevant to our hypothesis, we observed several diagnostic categories negatively associated with positive SARS-CoV-2 PCR test results, including actinic keratosis, ear and upper respiratory tract infection, and anxiety disorders ( Figure 2 A). When we analyzed specific ICD-10 codes, we found that conditions sometimes caused by CCC, including acute sinusitis and acute bronchitis and acute pharyngitis, were most significant ( Figure 2 B and Supplementary Table 2).…”
Section: Discussionsupporting
confidence: 73%
“…In accordance, our analysis identified several diagnostic categories that are significantly positively associated with a positive SARS-CoV-2 PCR test result, including diabetes, heart disease, obesity, and anemia, all of which others have also found to be associated with increased risk of COVID-19 hospitalizations ( Figure 2 A and Supplementary Table 1). 25 Relevant to our hypothesis, we observed several diagnostic categories negatively associated with positive SARS-CoV-2 PCR test results, including actinic keratosis, ear and upper respiratory tract infection, and anxiety disorders ( Figure 2 A). When we analyzed specific ICD-10 codes, we found that conditions sometimes caused by CCC, including acute sinusitis and acute bronchitis and acute pharyngitis, were most significant ( Figure 2 B and Supplementary Table 2).…”
Section: Discussionsupporting
confidence: 73%
“…We identified 20 studies that assessed the association between individuals with obesity and COVID‐19, all but two of which showed that individuals with obesity significantly increase the risk of COVID‐19 (Table S3). 25–43 One study in Denmark showed that the prevalence of overweight and individuals with obesity was lower in SARS‐CoV‐2 positive cases than SARS‐CoV‐2 test‐negative individuals (8.6% vs. 9.9%) 44 . The results may be biased because body weight status was determined at hospital discharge.…”
Section: Epidemiological Relationships: Individuals With Overweight Amentioning
confidence: 99%
“…Other variables included: age; sex; socioeconomic status using the index of multiple deprivation (IMD), based on lower super output area (LSOA) — a geographical subunit with a minimum population of 1000 — divided into quintiles; 13 ethnicity divided into white, Asian, black, mixed, and others; 14 and household size; determined using a pseudonymised household key based on identical address, this has been used in other studies. 10 , 15 , 16 smoking status (comparing current, ex- and non-smokers); obesity (using the World Health Organization categorisation of overweight [body mass index {BMI} = 25–29 kg/m 2 ]; obese [BMI = 30–34 kg/m 2 ]; and severely obese [BMI≥35 kg/m 2 ]; and population density (based on ONS locality data). 17 The highest population density was in ‘conurbations’, medium levels in ‘city and town’, and lowest density in ‘rural areas’.…”
Section: Methodsmentioning
confidence: 99%
“…household size; determined using a pseudonymised household key based on identical address, this has been used in other studies. 10 , 15 , 16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation